Differences in speed and body composition of basketball players depending on their position in the team - Mitic, M.; Kocic, M.; Beric, D.; Radovanovic, D.; Daskalovski, B. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
During a game of basketball the players are susceptible to different demands of offense and defense considering the characteristics of the game. To achieve top results in basketball, it is necessary to select the players with particular predispositions and characteristics. Basketball is comprised of a variety of fast, explosive and agile movements. The body composition of the players is different and it largely depends on the position in a team. However, it should be understood that there is no ideal body composition universal to all the sports. The sample of 15 players was divided into three groups depending on the position in a team (guards, forward and centres). The parameters which were the focal points of the research were the differences in speed (Shuttle Test, Sprint Fatigue Test and the Sprint Speed Test in 15m) and the body composition (applying the direct segmental multi-frequency method, using the InBody 770 analyzer). The differences between the players depending on their team position were established by ANOVA analysis for the independent samples and the subsequent Post hoc analysis. The results obtained show that there are no differences in speed. The most notable differences in the body composition between the players and in relation to the position they play are between guards and wings as are between guards and centres.